Peta Kapanca: Memandu Perjalanan Menuju Pernikahan Dalam Konteks Budaya Bima, Nusa Tenggara Barat - Azzahra, Fatimah; Rasmuin, Rasmuin (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
This research reviews the Peta Kapanca, an ancient tradition that guides marriage in Bima culture, West Nusa Tenggara, Indonesia. This research aims to understand the cultural values, customs, and rituals associated with the Peta Kapanca newlywed procession. A qualitative approach was used in this research, where the data collection methods were in-depth interviews and a literature review. The results showed that Peta Kapanca has a central role in guiding prospective brides and grooms in facing the transition stage toward marriage. The rituals involve family, traditional elders, and community leaders to provide the future bride and groom support, advice, and direction. Values such as cooperation, respect for ancestors, and family togetherness are the main foundations for implementing the Peta Kapanca. Overall, the Peta Kapanca is an integral part of the social and cultural life of the Bima people. This tradition plays an important role in preserving cultural values and local identity. Therefore, to ensure the continuity of the Peta Kapanca, the community and government need collaborative efforts to preserve and appreciate this valuable cultural heritage